Predikce vzniku a šíření těžkého plynu při chemických haváriích - Skřehot, Petr; Marek, Jakub; Houser, František; Hon, Zdeněk; Staněk, Martin; Melicharová, Michaela; Jaňour, Zbyněk; Korba, Peter (Chemické listy, 2019)
The development of human society, the increasing intensity of industrial production and transport activities associated with it have led to serious environmental im-pacts, especially air pollution. In addition to the common sources of emissions, various accidents also increasingly occur, including chemical leaks from production or transport facilities or large-scale industrial fires. Therefore, over the last thirty years, great efforts have been made to prevent chemical accidents. The key concern here is to understand the processes that affect the emergence and course of accidents as deeply as possible. One of the topics intensively studied in this context is the diffusion of heavy gas in a real atmosphere. This is a phenomenon with po-tentially very serious consequences; however, it is not easy to describe it physically and chemically. The dispersion of gas heavier than air is a complex process, determined by a number of various factors. Therefore, experts make efforts to understand this problem better, to gain new knowledge and to gradually refine existing dispersion models. One of such models is SLAB-DEGAS, which is a verified modifi-cation of the original SLAB model, created under Czech conditions.